Analisis Stres Kerja dan Konflik Kerja Terhadap Kinerja Pegawai Instalasi Bedah Sentral (IBS) RSUP Dr. Cipto Mangunkusumo Jakarta - Gus Andri (Universitas Peradaban, 2016)
The purpose of this study was to analyze the stress of work and conflict of work to employee performance Installation of Central Surgical Hospital Dr. Cipto Mangunkusumo. The method used is quantitative method. In this study, the population was an employee of the Central Surgical Hospital Installations Dr. Cipto Mangunkusumo totaling 73 people as well as a sample in this study with a total sampling technique. Based on these results it appears that stress of work variables significantly influence employee performance with a value of 1.244 regression with a significance level of 0.000 or <0.05. While the conflict of work variable significant effect on employee performance with a value of 0,349 regression with a significance level of 0.000 or < 0.05. At the t test for stress of work variables seen that t > t table (14.979 > 1.666). Where the effect of stress of work on performance amounted to 1,244, or 124.4%, with a probability of 0.000 or < 0.05. Then to variable conflict of work seen that t > t table (5.211> 1.666), where the influence of conflict of work on the performance of 0,349 or 3.49% with a probability of 0.000 or <0.05. In the F test seen that F count > F table (285.577 > 3.133) with a significance level of 0.000 or <0.05 consequently H0 and H1 accepted which means that stress of work variables and conflict of work jointly significant effect on employee performance. The coefficient of determination (adjusted R2) of 0.888 means that 88.8% of employee performance is affected by stress of work and conflict of work and 11.2% influenced by other variables.